Dicto-Comp in Indonesian’ English Writing Class - Nike Angraini; Jaya Nur Iman (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2022)
The present inquiry investigated the dicto-comp’ effectiveness on the writing achievement of EFL learners. An experimental research design, chiefly concerned on the non-equivalent pretest-posttest control group design, was taken into the research. Thirty six students were taken as the sample purposively. An English writing test was employed as the primary instrument to assess the writing achievement of EFL learners. The research results found out (1) the EFL learners’ English writing achievement level in the group of experimental after the treatment given was in the good and very good category, (2) dicto-comp significantly improved the EFL learners English writing achievement in the experimental group, and (3) dicto-comp made significant difference on EFL learners’ English writing achievement than those who were not. In conclusion, implementing dicto-comp improved the writing achievement of the EFL learners significantly. Pedagogical implications for English students and lecturers, stakeholder, and near future researchers were also made in this research.